2012
DOI: 10.1891/0739-6686.30.125
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering “Special Needs” Populations During a Disaster

Abstract: Meeting the "special needs" of at-risk populations affected by disasters is of the utmost importance. In the United States, there are 54 million people who fit into the special needs category who are defined as handicapped, disabled, vulnerable, challenged, or having special needs. The paramount importance for the special needs population is maintaining human dignity throughout the disaster management cycle. Government agencies, nongovernmental organizations, and advocacy organizations have all worked together… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…On the other hand, following disasters, some pre-existing medical problems may be aggravated (25,31,38,42,48).…”
Section: Pre-existing Medical Needsmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, following disasters, some pre-existing medical problems may be aggravated (25,31,38,42,48).…”
Section: Pre-existing Medical Needsmentioning
confidence: 99%
“…The findings of some studies showed that chronic diseases may interfere with older people's ability to evacuate; for example, somebody with the chronic obstructive pulmonary disease (COPD) who is trying to go down the stairs may face difficulty in evacuating (32,33,38,42). Moreover, chronic diseases can interfere with access to services after disasters; for example, a person with arthritis may have problems standing in line for access to services (32).…”
Section: Pre-existing Medical Needsmentioning
confidence: 99%
See 3 more Smart Citations